Renal Outcomes After Simultaneous Liver‐Kidney Transplantation: Results from the US Multicenter Simultaneous Liver‐Kidney Transplantation Consortium. Issue 8 (21st April 2021) - Sharma, Pratima; Sui, Zhiyu; Zhang, Min; Magee, John C.; Barman, Pranab; Patel, Yuval; Schluger, Aaron; Walter, Kara; Biggins, Scott W.; Cullaro, Giuseppe; Wong, Randi; Lai, Jennifer C.; et al.
Abstract : Simultaneous liver‐kidney transplantation (SLKT) is increasingly common in the United States. However, little is known about the renal‐related outcomes following SLKT, which are essential to maximize the health of these allografts. We examined the factors impacting renal function following SLKT. This is an observational multicenter cohort study from the US Multicenter SLKT Consortium consisting of recipients of SLKT aged ≥18 years of transplantations performed between February 2002 and June 2017 at 6 large US centers in 6 different United Network for Organ Sharing regions. The primary outcome was incident post‐SLKT stage 4‐5 chronic kidney disease (CKD) defined as <30 mL/minute/1.73 m 2 or listing for kidney transplant. The median age of the recipients (n = 570) was 58 years (interquartile range, 51‐64 years), and 37% were women, 76% were White, 33% had hepatitis C virus infection, 20% had nonalcoholic steatohepatitis (NASH), and 23% had alcohol‐related liver disease; 68% developed ≥ stage 3 CKD at the end of follow‐up. The 1‐year, 3‐year, and 5‐year incidence rates of post‐SLKT stage 4‐5 CKD were 10%, 12%, and 16%, respectively. Pre‐SLKT diabetes mellitus (hazard ratio [HR], 1.45; 95% CI, 1.00‐2.15), NASH (HR, 1.58; 95% CI, 1.01‐2.45), and delayed kidney graft function (HR, 1.72; 95% CI, 1.10‐2.71) were the recipient factors independently associated with high risk, whereas the use of tacrolimus (HR, 0.44; 95% CI, 0.22‐0.89) reduced the risk. Women (β = −6.22 ± 2.16 mL/minute/1.73 m 2 ; P = 0.004), NASH (β = −7.27 ± 3.27 mL/minute/1.73 m 2 ; P = 0.027), and delayed kidney graft function (β = −7.25 ± 2.26 mL/minute/1.73 m 2 ; P = 0.007) were independently associated with low estimated glomerular filtration rate at last follow‐up. Stage 4‐5 CKD is common after SLKT. There remains an unmet need for personalized renal protective strategies, specifically stratified by sex, diabetes mellitus, and liver disease, to preserve renal function among SLKT recipients.